An artifact-minimizing method for total dust sampling and chemical characterization of industrial high-temperature aerosols. Issue 9 (2nd September 2017) - Schumacher, Stefan; Lindermann, Jörg; Khot, Amit; Jarzyna, Dirk; Stahlmecke, Burkhard; Nordsieck, Hermann; Warnecke, Ragnar; Asbach, Christof
ABSTRACT: Conventional methods for total dust sampling from industrial high-temperature aerosols containing condensable species, e.g., in boilers of municipal solid waste incinerators (MSWI), are always influenced by condensation artifacts. Therefore, we extended the scope of a previously developed probe intended for size-fractionated aerosol sampling with reduced artifacts and employed it for total dust measurements. The dust is collected on quartz fiber filters, which are gravimetrically evaluated and chemically analyzed by energy dispersive X-ray spectroscopy and wet-chemical methods. First measurements in the boiler of an MSWI confirm that the probe is also suitable for artifact-minimized total dust sampling. The data are consistent with results from measurements with the size-fractionating method conducted in parallel. By combining the results of both sampling methods, we reveal the average chemical composition of the submicron particles in the aerosol, which is not accessible by one of the two methods alone. © 2017 American Association for Aerosol Research